Microcephalic osteodysplastic primordial dwarfism type II and pachygyria: Morphometric analysis in a 2‐year‐old girl. Issue 10 (3rd August 2020) - Rossi‐Espagnet, Maria C.; Dentici, Maria L.; Pasquini, Luca; Carducci, Chiara; Lucignani, Martina; Longo, Daniela; Agolini, Emanuele; Novelli, Antonio; Gonfiantini, Michaela V.; Digilio, Maria C.; Napolitano, Antonio; Bartuli, Andrea
Abstract: Microcephalic osteodysplastic primordial dwarfism (MOPD) type II is a rare disorder characterized by skeletal dysplasia, severe proportionate short stature, insulin resistance and cerebrovascular abnormalities including cerebral aneurysms and moyamoya disease. MOPD type II is caused by mutations in the pericentrin ( PCNT ) gene, which encodes a protein involved in centrosomes function. We report a 2 year old girl affected by MOPD type II caused by two compound heterozygous loss‐of‐function variants in PCNT gene, of which one is a novel variant (c.5304delT; p.Gly1769AlafsTer34). The patient presented atypical brain magnetic resonance imaging (MRI) findings consistent with pachygyria. This was confirmed by morphometric analysis of cortical thickness (CT) and gyrification index by comparing MRI data of the patient with a group of eight age‐matched healthy controls. The statistical analysis revealed a significant and diffuse increase of CT with an anterior‐predominant pattern and diffuse reduced gyrification ( p  < .05). These findings provide new evidences to the emergent concept that malformations of cortical development are complex disorders and that new genetic findings contribute to the fading of classification borders.